9
$\begingroup$

I have found myself faced with evaluating the following integral: $$\int_1^{\infty } \frac{(\ln x)^2}{x^2+x+1} \, dx. $$

Mathematica gives a closed form of $8 \pi ^3/(81 \sqrt{3})$, but I have no idea how to arrive at this closed form. I've tried playing around with some methods from complex analysis, but I haven't had much luck (it has been a while). Does anyone have any ideas? Thanks in advance!

$\endgroup$
  • $\begingroup$ So, you've tried contour integration? $\endgroup$ – Mark Viola Mar 11 '15 at 22:40
7
$\begingroup$

Shocked, shocked! that there is no contour integration yet. So, without further ado...

Note that

$$f(x) = \frac{\log^2{x}}{x^2+x+1} \implies f \left ( \frac1{x} \right ) = x^2 f(x) $$

Thus, $$\int_1^{\infty} dx \frac{\log^2{x}}{x^2+x+1} = \int_0^{1} \frac{\log^2{x}}{x^2+x+1} = \frac12 \int_0^{\infty} dx \frac{\log^2{x}}{x^2+x+1} $$

Now consider

$$\oint_C dz \frac{\log^3{z}}{z^2+z+1} $$

where $C$ is a keyhole contour of outer radius $R$ and inner radius $\epsilon$. Taking the limit as $R \to \infty$ and $\epsilon \to 0$, we get that the contour integral is equal to

$$\int_0^{\infty} dx \frac{\log^3{x} - (\log{x}+i 2 \pi)^3}{x^2+x+1} $$

or

$$-i 6 \pi \int_0^{\infty} dx \frac{\log^2{x}}{x^2+x+1} + 12 \pi^2 \int_0^{\infty} dx \frac{\log{x}}{x^2+x+1} +i 8 \pi^3 \int_0^{\infty} dx \frac{1}{x^2+x+1} $$

Note that the first integral is what we seek, the second integral is zero (by the same trick we applied above), and the third integral is relatively easy to find:

$$\int_0^{\infty} \frac{dx}{x^2+x+1} = \int_0^{\infty} \frac{dx}{(x+1/2)^2+3/4} = \frac{2}{\sqrt{3}} \left [\arctan{\frac{2}{\sqrt{3}} \left ( x+\frac12 \right )} \right ]_0^{\infty} = \frac{2 \pi}{3 \sqrt{3}}$$

The contour integral is also equal to $i 2 \pi$ times the sum of the residues at the poles of the integrand, which are at $z_+ = e^{i 2 \pi/3}$ and $z_- = e^{i 4 \pi/3}$. The sum of the residues is

$$\frac{-i 8 \pi^3/27}{i \sqrt{3}} + \frac{-i 64 \pi^3/27}{-i \sqrt{3}} = \frac{56 \pi^3}{27 \sqrt{3}}$$

Then

$$-i 6 \pi \int_0^{\infty} dx \frac{\log^2{x}}{x^2+x+1} = i 2 \pi \frac{56 \pi^3}{27 \sqrt{3}} - i 8 \pi^3 \frac{2 \pi}{3 \sqrt{3}} = -i \frac{32 \pi^4}{27 \sqrt{3}}$$

Thus,

$$\int_1^{\infty} dx \frac{\log^2{x}}{x^2+x+1} = \frac12 \int_0^{\infty} dx \frac{\log^2{x}}{x^2+x+1} = \frac{8 \pi^3}{81 \sqrt{3}} $$

$\endgroup$
  • $\begingroup$ Straight forward!! $\endgroup$ – Mark Viola Mar 12 '15 at 0:32
  • $\begingroup$ Just what I was looking for, Thanks! $\endgroup$ – stochasm Mar 12 '15 at 2:42
4
$\begingroup$

It can be observed that $x^{2} + x + 1 = (x-a)(x-b)$ where $a = e^{2\pi i/3}$ and $b = e^{-2\pi i/3}$. Now \begin{align} I &= \int_{1}^{\infty} \frac{ (\ln(x))^{2} }{ (x-a)(x-b) } \, dx = \frac{1}{a-b} \, \int_{1}^{\infty} \left( \frac{1}{x-a} - \frac{1}{x-b} \right) \, (\ln(x))^{2} \, dx. \end{align} From Wolfram Alpha the integral \begin{align} \int \frac{ (\ln(x))^{2} }{ x - a } dx = -2 Li_{3}\left( \frac{x}{a} \right) +2 \log(x) \, Li_{2} \left( \frac{x}{a} \right) + \log^{2}(x) \log\left( 1-\frac{x}{a} \right) \end{align} for which the integral in question becomes \begin{align} I &= \left[ \frac{-2}{a-b} \left(Li_{3}\left( \frac{x}{a} \right) - Li_{3}\left(\frac{x}{b} \right) \right) + \frac{2}{a-b} \log(x) \, \left(Li_{2} \left( \frac{x}{a} \right) - Li_{2}\left( \frac{x}{b} \right) \right) + \frac{1}{a-b} \, \log^{2}(x) \log\left( \frac{a-x}{b-x} \right) \right]_{1}^{\infty} \\ &= \frac{-2}{a-b} \left[ Li_{3}\left( \frac{1}{a} \right) - Li_{3}\left(\frac{1}{b} \right) \right]. \end{align} This can then be seen as \begin{align} I &= \frac{-2i}{\sqrt{3}} \left[ Li_{3}\left( e^{2\pi i/3} \right) - Li_{3}\left( e^{- 2\pi i/3} \right) \right] \\ &= \frac{-2 i}{\sqrt{3}} \cdot \frac{4 \pi^{3} i}{81} = \frac{8 \pi^{3}}{81 \sqrt{3}}. \end{align}

\begin{align} \int_{1}^{\infty} \frac{ (\ln(x))^{2} }{ x^{2} + x + 1 } \, dx = \frac{8 \pi^{3}}{81 \sqrt{3}}. \end{align}

$\endgroup$
4
$\begingroup$

Hint: In general, $~I_n(k)~=~\displaystyle\int_0^\infty\frac{x^{k-1}}{1-x^n}~dx~=~\frac\pi n~\cot\bigg(k~\frac\pi n\bigg),~$ see Cauchy principal value.

At the same time, a simple substitution of the form $t=\dfrac1x$ shows that the original integral can be

written as $J=\displaystyle\int_1^\infty f(x)~dx~=~\int_0^1f(x)~dx~=~\frac12~\int_0^\infty f(x)~dx.~$ Then, by rewriting the

integrand using $\dfrac1{x^2+x+1}=\dfrac{1-x~}{1-x^3}~,~$ we have $J=\dfrac{I_3''(1)-I_3''(2)}2$.

$\endgroup$
4
$\begingroup$

Here is an approach.

Observe that $$ I:=\int_1^{\infty } \frac{(\ln x)^2}{x^2+x+1} \, dx=\int_1^{\infty } \frac{(x-1)(\ln x)^2}{x^3-1} \, dx $$ and by the change of variable $x \to 1/x$ $$ I=\int_0^1 \frac{(1-x)\color{blue}{(\ln x)^2}}{1-x^3} \, dx. \tag1 $$ Since $\displaystyle \color{red}{\partial_s^2\color{red}{ (x^s)}|_{\large s=0}}=\color{blue}{(\ln x)^2}$, one may write that $$ I=\left.\color{red}{\partial_s^2}\left(\int_0^1 \frac{x^s(1-x)}{1-x^3} \, dx\right)\right|_\color{red}{{\large s=0}} \tag2 $$ Now $$ \begin{align} \int_0^1 \frac{x^s(1-x)}{1-x^3} \, dx&=\frac13\int_0^1 \frac{u^{(s-2)/3}-u^{(s-1)/3}}{1-u} \, du\qquad (u=x^3,\,x=u^{1/3})\\\\ &=\frac13\int_0^1 \frac{(1-u^{(s-1)/3})-(1-u^{(s-2)/3})}{1-u} \, du\\\\ &=\frac13\int_0^1 \frac{1-u^{(s-1)/3}}{1-u} \, du-\frac13\int_0^1 \frac{1-u^{(s-2)/3}}{1-u} \, du\\\\ &=\frac13\psi\left(\frac{s+2}{3}\right)-\frac13\psi\left(\frac{s+1}{3}\right) \tag3 \end{align} $$ where we have used the standard integral representation for the digamma function.

Then using $(2)$, we get $$ I=\frac1{27}\psi''\!\!\left(\frac{2}{3}\right)-\frac1{27}\psi''\!\!\left(\frac{1}{3}\right)=\frac{8\pi^3}{81\sqrt{3}} $$ taking into account some special values of $\psi''$.

$\endgroup$
2
$\begingroup$

Note $$ \int_0^1x^m(\ln x)^2dx=\frac{2}{(m+1)^3} $$ So \begin{eqnarray} I&=&\int_1^{\infty } \frac{(\ln x)^2}{x^2+x+1}dx\\ &=&\int_0^1\frac{(1-x)(\ln x)^2}{1-x^3}dx\\ &=&\int_0^1\sum_{n=0}^\infty(1-x)x^{3n}(\ln x)^2dx\\ &=&2\sum_{n=0}^\infty\left(\frac{1}{(3n+1)^3}-\frac{1}{(3n+2)^3}\right)\\ &=&2\sum_{n=-\infty}^\infty\frac{1}{(3n+1)^3} \end{eqnarray} Note \begin{eqnarray} \sum_{n=-\infty}^\infty\frac{1}{(3n+1)^3}=-\pi\text{Res}(\frac{1}{(z+1)^3}\cot(\pi z),-\frac{1}{3})=\frac{4\pi^3}{81\sqrt3} \end{eqnarray} and hence $$ I=\frac{8\pi^3}{81\sqrt3}. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.